Piceatannol-rich extract from Passiflora edulis Sims seeds attenuates morphological differentiation through the reduction of MITF mRNA expression and F-actin polymerization in UVB-induced hyperpigmented B16F10 cells - Paween Kunsorn; Witchuda Payuhakrit; Nasapon Povichit; Prasit Suwannalert (GarVal Editorial Ltda., 2024)
Context: Ultraviolet B (UVB) light irradiation causes skin problems by increasing cellular oxidants, melanogenesis, and morphological changes of melanocytes. The use of active compounds derived from plants to mitigate these problems has been studied. Piceatannol (PCT), a phytochemical in the phenolic group contained in Passiflora edulis fruit seed (PFS), has gained interest for its anti-melanogenesis effects. However, the inhibitory effect on morphological differentiation related to melanin production of PFS extract is absent. Aims: To investigate the effect of PFS extract on the inhibition of morphological differentiation associated with microphthalmia-associated transcription factor (MITF) mRNA expression and F-actin polymerization in UVB-induced hyperpigmented B16F10 cells. Methods: Three fractions of PFS extract were analyzed for their total phenolics, PCT proportion, and antioxidant capacity. The fraction with the highest PCT proportion and antioxidant activity was investigated for its reductive effects on cellular oxidants, number of melanin-containing cells, melanin content, MITF mRNA expression, and tyrosinase activity in UVB-induced B16F10 cells. Morphological differentiation, as well as F-actin polymerization and arrangement, were analyzed. Results: The PFS-F3 extract showed the highest antioxidant effect related to the proportion of PCT and phenolic contents. It attenuated cellular oxidants, the number of melanin-containing cells, melanin content, MITF mRNA expression, and tyrosinase activity. Differentiation, polymerization, and the arrangement of F-actin of most UVB-irradiated cells were repressed after treatment with the extract. Conclusions: The PFS extract rich in PCT attenuated morphological differentiation by suppressing the functions of MITF mRNA and F-actin polymerization through the reduction of cellular oxidants, resulting in a decrease in melanin production.